Violence and emotions in early modern Europe
1 online resource (xv, 213 pages)
Keywords: "Violence and Emotions in Early Modern Europe examines the purposes for which specific forms of violence and particular emotional states functioned, how they operated in relation to each other, or indeed how one provoked, sustained or diminished the other"--Provided by publisher.